2000
DOI: 10.1046/j.1467-2979.2000.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecoepidemiology of the effects of pollution on reproduction and survival of early life stages in teleosts

Abstract: Evidence from the field and laboratory has shown that reproduction and early life‐stage survival of several species of teleost fishes have been adversely affected following the release of several classes of synthetic, organic chemicals into the environment. Field studies from many geographic areas over several decades have found associations between exposure to synthetic chemicals in the environment and effects on hatchability, embryological success and larval survival. In more recent research, exposure to sew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 139 publications
0
13
0
1
Order By: Relevance
“…Hepatic EROD activity has commonly been employed as a biomarker for exposure to substances binding to the arylhydrocarbon receptor (AhR) such as polynuclear aromatic hydrocarbons (PAHs), and persistent polyhalogenated aromatic hydrocarbons (PHAHs) such as dioxins, furans and polychlorinated biphenyls (Altenburger et al, 2003;Whyte et al;2000;van der Oost et al, 2003). Exposure to PAHs and PHAHs can have adverse consequences on fi sh health and population growth: these xenobiotics are known to adversely affect early life stage survival, development and reproduction of fi sh (Fairbrother et al, 1999;Rolland, 2000;Altenburger et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hepatic EROD activity has commonly been employed as a biomarker for exposure to substances binding to the arylhydrocarbon receptor (AhR) such as polynuclear aromatic hydrocarbons (PAHs), and persistent polyhalogenated aromatic hydrocarbons (PHAHs) such as dioxins, furans and polychlorinated biphenyls (Altenburger et al, 2003;Whyte et al;2000;van der Oost et al, 2003). Exposure to PAHs and PHAHs can have adverse consequences on fi sh health and population growth: these xenobiotics are known to adversely affect early life stage survival, development and reproduction of fi sh (Fairbrother et al, 1999;Rolland, 2000;Altenburger et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to PAHs and PHAHs can have adverse consequences on fi sh health and population growth: these xenobiotics are known to adversely affect early life stage survival, development and reproduction of fi sh (Fairbrother et al, 1999;Rolland, 2000;Altenburger et al, 2003). At fi eld sites with elevated PAH and/or PHAH contamination, such as the Puget Sound or the Great Lakes in Northern America, increased prevalence of toxicopathic lesions and neoplasms (Myers et al, 1998;Stehr et al; as well as population declines have been reported (Monosson, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hill [60], suggested nine epidemiological criteria to be used when a correlation is observed between an exposure and an effect, to help decide whether there is a case for inferring that exposure causes the effect: strength of association, consistency of association, speci-ficity of association, time order, biological gradient/dose-response relation, biological plausibility, coherence, experimental evidence, and analogy. The usefulness and applicability of the weight-of-evidence approach and epidemiological criteria in an ecological context is demonstrated in the review of Rollands [61], upon the effects of pollution on reproduction and survival of early life stages in teleosts. An important step for the success of a monitoring study is the definition of which questions the study is actually supposed to answer and in what detail.…”
Section: Integrated Chemical-biological Monitoringmentioning
confidence: 99%
“…Όπως έδει ξε στην ανασκόπηση του ο Rolland (2000), πολλές επι βαρυντικές χημικές ουσίες που υπάρχουν στο νερό και ανιχνεύονται στα ώριμα θηλυκά, ανιχνεύονται στη συ νέχεια και στα αβγά τους. Ένας τρόπος για την απο τίμηση της αναπαραγωγικής υγείας των ψαριών είναι μέσω της ποιότητας των ωοκυττάρων που παράγουν.…”
unclassified